2015
DOI: 10.3390/molecules20011277
|View full text |Cite
|
Sign up to set email alerts
|

Bisdemethoxycurcumin Induces Apoptosis in Activated Hepatic Stellate Cells via Cannabinoid Receptor 2

Abstract: Activated Hepatic Stellate Cells (HSCs), major fibrogenic cells in the liver, undergo apoptosis when liver injuries cease, which may contribute to the resolution of fibrosis. Bisdemethoxycurcumin (BDMC) is a natural derivative of curcumin with anti-inflammatory and anti-cancer activities. The therapeutic potential of BDMC in hepatic fibrosis has not been studied thus far in the context of the apoptosis in activated HSCs. In the current study, we compared the activities of BDMC and curcumin in the HSC-T6 cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…[24][25][26][27] Thus, the oxidative stress induced by ROS contributes to neuronal cell death in the brain. [24][25][26][27] Similar to these findings, we detected significantly high ROS levels in HT-22 cells after treatment with TG. On the contrary, inhibition of ROS generation by betulin was comparable with that caused by TUDCA, after treatment with TG ( Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27] Thus, the oxidative stress induced by ROS contributes to neuronal cell death in the brain. [24][25][26][27] Similar to these findings, we detected significantly high ROS levels in HT-22 cells after treatment with TG. On the contrary, inhibition of ROS generation by betulin was comparable with that caused by TUDCA, after treatment with TG ( Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…Heme oxygenase-1 (HO-1) is an enzyme that catalyzes the breakdown of heme into the antioxidant biliverdin, CO, and iron. 26 HO-1 has received considerable attention for the potential neuroprotective effects in cell death models. 27,28 We used hemin, an HO-1 inducer, and SnPP, an HO-1 inhibitor, to investigate whether HO-1 is involved in ER stress-induced cytotoxicity in HT-22 cells by assessing the cell viability by measuring the ROS levels (Figure 3a and b).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study also showed that DMC induced the apoptosis of human lung cancer NCI‐H460 cells through the mitochondrial‐dependent pathway . BDMC inhibited adipogenesis in 3T3‐L1 preadipocytes and it had the potential to prevent obesity and induced cell apoptosis in human laryngeal carcinoma cells, activated hepatic stellate cells, and lung cancer NCI‐H460 cells . In human fibrosarcoma cells, DMC or BDMC had higher anti‐metastasis potency than that of CUR via the differentially downregulation of ECM degradation enzymes …”
Section: Introductionmentioning
confidence: 93%
“…Animal tissues were lysed with radioimmunoprecipitation assay (RIPA) buffer [1 × PBS, 1% (v/v) Non-idet P-40 (NP-40), 0.5% (w/v) sodium deoxycholate, 0.1% (w/v) sodium dodecyl sulfate (SDS), 0.1 mg/mL phenylmethylsulfonyl fluoride (PMSF), 30 ”l/mL aprotinin, and 1 mM sodium orthovanadate (Na 2 VO 3 )], and homogenized by sonication (Lee et al, 2015). Total tissue lysates were centrifuged and the resulting supernatants were collected.…”
Section: Western Blottingmentioning
confidence: 99%